Upaya Peningkatan Kelincahan dan Kecepatan dalam Bermain Sepak Bola melalui Metode Demonstrasi pada Siswa Kelas V SD Negeri 6 Ampenan - Sulistiani, Endang (ARZUSIN, 2022)
Speed ​​and agility are the basic models in playing football and for players are the capital of success to score goals, and keep goals conceded. With the ability to speed will make it easier for players to carry the ball. The problems to be studied in this research are: (a) How to improve the achievement of mastery of the basics of football for students in the implementation of the demonstration method? (b) How is the effect of the demonstration method on students' learning motivation? The aims of this study were (a) to find out the improvement in students' learning achievement of the basics of football after the implementation of the demonstration method, (b) to find out the motivation to learn the basics of football after the implementation of the demonstration method. This study uses two rounds of action research. Each round consists of two stages, namely: design, activity and observation. Reflection and revision The target of this research is the fifth grade students of SD Negeri 06 Ampenan for the 2019/2020 academic year. From the data obtained in the form of practice test results, observation sheets for teaching and learning activities. cycle I (61.54%), cycle II (89.74%) for the psychomotor domain, cycle I (84.62%) Cycle II (100%) for the active domain. The conclusion of this study is that the demonstration method can have a positive effect on the learning motivation of Class V students at SD Negeri 06 Ampenan for the 2019/2020 academic year. and the learning model can be used as an alternative PJOK.